2001
DOI: 10.1007/bf02298958
|View full text |Cite
|
Sign up to set email alerts
|

Changes of gastric emptying rate and gastrin levels are early indicators of autonomic neuropathy in type II diabetic patients

Abstract: The authors investigated the effect of a balanced meal on gastric emptying rate and gastrin plasma concentrations in patients with type II diabetes and autonomic neuropathy, in diabetic patients without autonomic neuropathy, and in healthy subjects (controls). Before food the gastrin plasma concentrations were higher in patients with diabetes with autonomic neuropathy. After food, gastric emptying rate was slower in patients with diabetes with autonomic neuropathy, whereas gastrin plasma concentrations increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…This process is regulated by a negative feedback mechanism to prevent excessive acid secretion. In accordance with earlier studies we found that patients with autonomic neuropathy have significantly higher concentrations of gastrin in plasma [16-18,20]. The elevated gastrin concentrations cannot be explained by atrophic gastritis in this study since only one subject had this condition.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This process is regulated by a negative feedback mechanism to prevent excessive acid secretion. In accordance with earlier studies we found that patients with autonomic neuropathy have significantly higher concentrations of gastrin in plasma [16-18,20]. The elevated gastrin concentrations cannot be explained by atrophic gastritis in this study since only one subject had this condition.…”
Section: Resultssupporting
confidence: 93%
“…Cholecystokinin (CCK) and gastrin are released from endocrine cells in the upper GI tract in response to food, and they influence relaxation of the lower oesophageal sphincter (LOS), gastric acid secretion, gastric emptying, growth of gastric mucosa, contraction of the gallbladder, pancreatic growth, enzyme secretion, and intestinal motility [14,15]. Earlier studies have reported increased CCK and gastrin concentrations in plasma from diabetics with autonomic neuropathy [16-20], whereas patients without neuropathy showed normal concentrations, irrespective of GI function [17,19-21]. Recently, receptors for vasopressin, a peptide hormone homologous to oxytocin, have also been found in the GI tract [22], and vasopressin has been shown to affect the electrical rhythm in the human stomach [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In 34 individuals with T2DM, the gastric emptying rate was slower in the group with CAN (n=16) compared to the group without CAN (n=18) and the control subjects (n=18) [37]. Furthermore, a positive correlation was found between degree of autonomic dysfunction and gastric emptying rate for both solids and liquids.…”
Section: Autonomic Neuropathymentioning
confidence: 92%
“…In our case, the patient had none of these symptoms and hence had never been diagnosed as having diabetic gastroparesis. However, recent studies have suggested that slowed gastric emptying is present in patients with autonomic neuropathy without any symptoms of gastroparesis [3]. Furthermore, the relation between symptoms and the rate of gastric emptying is weak, and the mechanisms by which abnormal motility causes symptoms are unclear [4][5][6].…”
Section: Discussionmentioning
confidence: 99%